2008
DOI: 10.1103/physrevlett.101.054801
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Trains of Electron Microbunches with Adjustable Subpicosecond Spacing

Abstract: We demonstrate that trains of subpicosecond electron microbunches, with subpicosecond spacing, can be produced by placing a mask in a region of the beam line where the beam transverse size is dominated by the correlated energy spread. We show that the number, length, and spacing of the microbunches can be controlled through the parameters of the beam and the mask. Such microbunch trains can be further compressed and accelerated and have applications to free electron lasers and plasma wakefield accelerators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
138
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 152 publications
(145 citation statements)
references
References 16 publications
5
138
0
Order By: Relevance
“…As way of background, it has been demonstrated in experiments that when propagating in uniform plasmas, e þ beams drive smaller amplitude wakefields than e À beams with similar parameters [13]. It was also observed that these positron beams develop a charge halo [14]. As expected, numerical simulations show that the nonlinear plasma focusing force creating the halo also leads to emittance growth [14].…”
Section: B Simulations Of Positron Pwfa In Hollow Plasma Channelsupporting
confidence: 49%
See 2 more Smart Citations
“…As way of background, it has been demonstrated in experiments that when propagating in uniform plasmas, e þ beams drive smaller amplitude wakefields than e À beams with similar parameters [13]. It was also observed that these positron beams develop a charge halo [14]. As expected, numerical simulations show that the nonlinear plasma focusing force creating the halo also leads to emittance growth [14].…”
Section: B Simulations Of Positron Pwfa In Hollow Plasma Channelsupporting
confidence: 49%
“…It was also observed that these positron beams develop a charge halo [14]. As expected, numerical simulations show that the nonlinear plasma focusing force creating the halo also leads to emittance growth [14]. However, simulations also indicate that larger gradients can be driven in hollow plasma channels than in uniform plasmas [6].…”
Section: B Simulations Of Positron Pwfa In Hollow Plasma Channelmentioning
confidence: 83%
See 1 more Smart Citation
“…This method is simple, but yields wide band THz radiation. This method in fact is used in CTR (coherent transition radiation) interferometry to determine the bunch spacing in the train [12,14,17]. Alternatively one can use an undulator, creating a THz free electron laser (FEL).…”
Section: Thz Extractionmentioning
confidence: 99%
“…Such microbunching can be produced at the photocathode by means of laser microbunches spaced at subpicosecond intervals [7,8]. Alternatively one can start with a longer electron beam and perform bunch compression [9,10] and/or use a beam masking technique in conjunction with phase space manipulation systems, like an emittance exchanger [11,12] to produce required bunching. We propose to use the beam's self-wake action along with compression in a chicane to introduce THz content into the beam.…”
Section: Production Of a Thz Beammentioning
confidence: 99%